1948
DOI: 10.1021/ie50459a024
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Formaldehyde with Casein

Abstract: Graphs are presented to show the effects of concentration of formaldehyde, pH, time, and temperature on the amount of recoverable formaldehyde remaining in combination with casein after exhaustive washing of the reaction product with distilled water. The results are compared with related data of other investigators and are discussed in terms of possible reactions of various structural units in the protein. The analytical procedures employed for distillation and titration of recoverable formaldehyde were extens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1948
1948
1983
1983

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 9 publications
(19 reference statements)
0
6
0
Order By: Relevance
“…Swain et al [ 15 ] also found a rapid increase in the binding of formaldehyde by casein as the temperature was increased to 60°C. At this temperature, under the conditions employed, the binding capacity of casein appears to be saturated because no further increase in binding was obtained by raising the temperature to 85 ° C.…”
Section: Methodsmentioning
confidence: 91%
See 3 more Smart Citations
“…Swain et al [ 15 ] also found a rapid increase in the binding of formaldehyde by casein as the temperature was increased to 60°C. At this temperature, under the conditions employed, the binding capacity of casein appears to be saturated because no further increase in binding was obtained by raising the temperature to 85 ° C.…”
Section: Methodsmentioning
confidence: 91%
“…We have used the technique developed and described by Swain et al [15] in carrying out the distillation and bisulfite titration of formaldehyde. This method does not determine irreversibly bound formaldehyde and we have made no studies toward evaluating this factor.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The assessment of the amount of formaldehyde bound to the protein is a major problem. It is difficult to recover all of the bound formaldehyde by conventional methods such as distillation from hot concentrated phosphoric acid solution (Swain et al 1948;Middlebrook 1949; Reddie and Nicholls 1971). [14C]Formaldehyde was used in most of the present experiments to provide a simple and convenient way of assessing the total amount of formaldehyde carbon which remained in the products after subjecting them to a standard washing procedure. The amount of 14C in these products was taken as an index of "bound formaldehyde".…”
Section: Introductionmentioning
confidence: 99%